2013
DOI: 10.5194/acp-13-8543-2013
|View full text |Cite
|
Sign up to set email alerts
|

Possible effect of extreme solar energetic particle events of September–October 1989 on polar stratospheric aerosols: a case study

Abstract: Abstract. The main ionization source of the middle and low Earth's atmosphere is related to energetic particles coming from outer space. Usually it is ionization from cosmic rays that is always present in the atmosphere. But in a case of a very strong solar eruption, some solar energetic particles (SEPs) can reach middle/low atmosphere increasing the ionization rate up to some orders of magnitude at polar latitudes. We continue investigating such a special class of solar events and their possible applications … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…These figures confirm the conclusion by Usoskin et al . [] and Mironova and Usoskin [] that ion pair production rates in the lower stratosphere are 1–2 orders of magnitude less than in the midstratosphere, even during hard spectrum events.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These figures confirm the conclusion by Usoskin et al . [] and Mironova and Usoskin [] that ion pair production rates in the lower stratosphere are 1–2 orders of magnitude less than in the midstratosphere, even during hard spectrum events.…”
Section: Resultssupporting
confidence: 91%
“…These enhancements are similar in relative magnitude to the twofold to fivefold nitrate spikes measured in Greenland ice cores and attributed to SPEs. 1972, October 1989, January 2012, and March 2012and GCR rates (annual mean) from 1972[Usoskin et al, 2010Mertens et al, 2013;Jackman et al, 2014]. Journal of Geophysical Research: Atmospheres 10.1002/2015JD023805 By placing these hypothetical SPEs in the context of probability distributions and upper limit estimates, we can assess the frequency that such events might occur and consequently the potential usefulness of nitrate as a proxy for individual SPEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction makes it difficult to utilise regression or superposed epoch analysis in statistical studies of cosmic ray events. Reflecting this, atmospheric impacts of individual GLE events were analysed for 1989 (Mironova and Usoskin 2013(Mironova et al 2012), and 2000, 2001and 2003(Mironova and Usoskin 2014. The results suggested that an enhancement of ionisation rate by a factor of about 2 in the polar region with the night/cold/winter conditions can lead to formation or growing of aerosol particles in the polar middle stratosphere.…”
Section: Cosmic Raysmentioning
confidence: 99%
“…A number of publications have studied the effects of transient solar events (SEP or ground level enhancement (GLE) of CR) on the lower stratosphere and upper troposphere in the polar regions (Calisto et al 2013;Mironova et al 2012;Mironova and Usoskin 2013;Mironova and Usoskin 2014;Usoskin et al 2011), including calculation of atmospheric ionisation from nearly all GLE events since 1956. The results indicated that there is no straightforward relation between the strength of the GLE events (as measured by neutron monitors) and the ionisation effect in polar atmosphere.…”
Section: Cosmic Raysmentioning
confidence: 99%